2007
DOI: 10.1111/j.1365-2427.2007.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue nutrient concentrations in freshwater aquatic macrophytes: high inter‐taxon differences and low phenotypic response to nutrient supply

Abstract: 1. The elemental composition and stoichiometry of aquatic plants has often been suggested to reflect the nutrient enrichment of aquatic habitats. However, the relationship is often weak. Moreover, uncertainties remain in the relevance of laboratory derived critical plant tissue nutrient concentrations to maximum yield or growth rates in the field. 2. Aquatic vascular plants and bryophytes, overlying water and sediment samples were collected to test whether freshwater aquatic macrophytes: (i) show tissue nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
106
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 37 publications
14
106
4
2
Order By: Relevance
“…The mean concentration of tissue C in our study was much lower than 438 mg g −1 reported by Demars and Edwards (2007). This result was consistent with the previous study in eastern China and mid-lower Yangtze floodplain lakes (Xia et al 2014;Xing et al 2013).…”
Section: Discussion C:n:p Stoichiometric Characteristics Of Submergedsupporting
confidence: 82%
See 3 more Smart Citations
“…The mean concentration of tissue C in our study was much lower than 438 mg g −1 reported by Demars and Edwards (2007). This result was consistent with the previous study in eastern China and mid-lower Yangtze floodplain lakes (Xia et al 2014;Xing et al 2013).…”
Section: Discussion C:n:p Stoichiometric Characteristics Of Submergedsupporting
confidence: 82%
“…In our study, the mean C:N:P mass ratio of macrophytes was approximately 191:12:1, lower than (except N:P ratio) the ratio of growth rate limitation (272:11:1) reported by Demars and Edwards (2007) for macrophytes in the River Spey in Great Britain. The mean concentration of tissue C in our study was much lower than 438 mg g −1 reported by Demars and Edwards (2007).…”
Section: Discussion C:n:p Stoichiometric Characteristics Of Submergedmentioning
confidence: 46%
See 2 more Smart Citations
“…Chinese Journal of Plant Ecology, 40, 1124Ecology, 40, -1135Ecology, 40, . doi: 10.17521/cjpe.2016 人类活动导致大气氮(N)沉降不断增强 (Galloway et al, 2004;Dentener et al, 2006;Mahowald et al, 2008), 正深刻影响着生态系统及其养分循环过程 (Vitousek & Tilman, 1997;Galloway & Sutton, 2008;Treseder, 2008)。野外人工N添加实验是模拟自然N 沉降增加对生态系统影响的重要手段。自20世纪80 年代起, 研究者在温带和北方森林地区陆续开展了 大 量 长 时 间 的 野 外 N 添 加 实 验 (Aber & Melillo, 1989;Wright & Rasmussen, 1998;Magill et al, 2000Magill et al, , 2004, 而N添加实验在亚热带常绿阔叶林地区开展 得相对较少 (Mo et al, 2008;Lu et al, 2010)。我国的 亚热带常绿阔叶林面积广阔、 物种组成丰富 (Fang et al, 2014), 是全球亚热带常绿阔叶林的主要分布区, 在我国亚热带常绿阔叶林地区开展N添加的生态学 效应的研究十分必要。 在全球变化的背景下, 植物的化学计量特征可 以 表 征 植 物 维 持 体 内 化 学 计 量 内 稳 性 的 能 力 (Sterner & Elser, 2002;Demars & Edwards, 2007), 并 反映植物对环境变化的适应性 (Elser et al, 2010a)。 以往的研究表明, 植物叶片N、磷(P)化学计量特征 因植被类型、功能群、物种的差异而不同 (Sterner & Elser, 2002;Reich, 2003;Ågren, 2004), 不同功能群 和 物 种 对 N 添 加 的 响 应 也 存 在 差 异 (Güsewell, 2004)。自20世纪80年代起, 研究人员在温带和北方 森林地区陆续开展了一些经典的野外N添加实验 (Aber & Melillo, 1989;Wright & Rasmussen, 1998;Magill et al, 2000), 植物化学计量学作为研究N循 环的新手段, 也被应用于N添加生态学效应的研究 …”
unclassified